Guided Wave Propagation for Monitoring the Rail Base. (8th August 2020) - Yue, Guodong; Cui, Xiushi; Zhang, Ke; Wang, Zhan; An, Dong
Abstract : In order to monitor the rail base, the dispersion characteristics and propagation properties of the guided wave are studied. Firstly, two modes named as Modes V 1 and V 2 are selected by the semianalytical finite element method (SAFE). The region at the bottom edge can be monitored by Mode V 1, while the junction of the base edge and the flange can be detected by Mode V 2 . Then, the characteristics in the propagation process are analyzed using the finite element method (FEM). The two modes can be separated about 0.6 ms after they are excited. Thirdly, a wave attenuation algorithm based on mean is proposed to quantify the wave attenuation. Both waves can have weak attenuation and be detected within 5 m. Finally, a mode-identified experiment is performed to validate the aforementioned analysis. And a defect detection experiment is performed to demonstrate the excellent monitoring characteristics using Mode V 2 . These results can be used to monitor the rail base in practice engineering.